2022
DOI: 10.1111/aphw.12426
|View full text |Cite
|
Sign up to set email alerts
|

The effects of virtual reality‐based exercise in adults receiving haemodialysis treatment: A systematic review and meta‐analysis of randomized controlled studies

Abstract: This meta‐analysis aimed to synthesize the effects of virtual reality‐based exercise on physical function, depression symptoms and quality of life in adults receiving haemodialysis. Data were analysed using Comprehensive Meta‐Analysis Version 3. The random‐effects meta‐analysis was performed to pool intervention effects. A total of five studies were included. The majority of included studies compared intervention with passive control group. This meta‐analysis showed with a moderate to high quality of evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition to an expanded range of programs, VR applications could be individualized for HD patients (f. e. applications to improve cognitive skills or health literacy in the context of nutrition and activity). VR applications in the context of an intradialytic physical exercise program seem to be effective and feasible [ 56 58 ]. Therefore, in the context of an integrated intradialytic sports program, VR could also serve as motivation accelerator for HD patients who can do physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an expanded range of programs, VR applications could be individualized for HD patients (f. e. applications to improve cognitive skills or health literacy in the context of nutrition and activity). VR applications in the context of an intradialytic physical exercise program seem to be effective and feasible [ 56 58 ]. Therefore, in the context of an integrated intradialytic sports program, VR could also serve as motivation accelerator for HD patients who can do physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…During the analysis of the literature, research using virtual reality exercises, the aim of which was to improve physical fitness in groups of people treated with dialysis, has been found 5 , 55 . In addition, it has been shown that the use of virtual reality during intradialytic exercises increases physical activity, improves physical fitness and the quality of life of persons undergoing dialysis 4 .…”
Section: Discussionmentioning
confidence: 99%